A Rab1 homologue with a novel isoprenylation signal provides insight into the secretory pathway of Theileria parva - Janoo, R.T.K.; Musoke, A.J.; Wells, C.; Bishop, Richard P. (Elsevier, 1999)
As a first step in developing compartment-specific markers for protein trafficking within Theileria parva, we have isolated cDNAs encoding homologues of the small GTP binding proteins Rab1 and Rab4. The T. parva homologue of Rab1 (TpRab1), a protein which regulates vesicular transport between the endoplasmic reticulum and cis golgi in other organisms, was unusual in that it contained a unique 17 amino acid C-terminal extension. The C-terminal motifisequence KCT (XCX) contrasted with the CXC or XCC motifs which act as signals for isoprenylation by geranylgeranyl in most Rab proteins, including all known Rab1 homologues, in containing only a single cysteine, (C14) mevalonic acid lactone and (H3) geranylgeranyl pyrophosphate were specifically incorporated into recombinant TpRab1 in vitro, demonstrating that the novel motif was functional for isoprenylation. Recombinant TpRab1 bound radiolabeled GTP, and this binding was inhibited by excess unlabeled GTP and GDP and also partially by ATP. The TpRab1 gene contained four short (34-67 bp) introns with a distinct pattern of occurrence within the protein sequence as compared to the introns of other lower eukaryote Rab1 genes. Immunofluorescence microscopy using antiserum specific for the novel C-terminal peptide in combination with labelling of cells using the nucleic acid-staining dye DAPI, indicated that TpRab1 was located in the vicinity of the schizont nucleus within the infected lymphocyte.